Teologi Liberal Muhammad Syahrur: Dekonstruksi-Rekonstruksi Pemikiran Klasik, Rukun Islam, dan Rukun Iman: Muhammad Syahrur's Liberal Theology: Deconstruction-Reconstruction of Classical Thought, the Pillars of Islam, and the Pillars of Faith - Almutawallid, Almutawallid; Barsihannor, Barsihannor; Santalia, Indo (Jurnal Filsafat Indonesia, 2024)
This article aims to objectively analyse Muhammad Syahrur's main ideas. This article uses the approach of hermeneutics and Islamic theology, the method used in this article is descriptive analysis. The descriptive analysis method is used to explain how Muhammad Syahrur's theological thought and the concept of deconstruction and reconstruction of the pillars of Faith and Islam. This type of research is library research. The results of this article reveal the focal point of Muhammad Syahrur's criticism is the classical interpretation books and their rules that have been considered established and final, the attitude of the establishment of classical scholars makes Islam lag far behind in the field of science that ignores the needs of the times and its development, the fundamental problem is the absence of scientific and empirical methods making it outdated in the current context by presenting scientific and hermeneutic sciences in the rules of interpretation according to him much more relevant and reasonable seeing technology and science continue to advance. Therefore, there needs to be a deconstruction-reconstruction of the books and rules of interpretation including the pillars of Islam and Iman. Muhammad Syahrur formulated his own new pillars of Faith and Islam, considered to be more relevant to the needs of the times and more humane, according to him the pillars of Islam and Faith that have been maintained from the past until now are not in accordance with human instincts and are contrary to the times.